Prognostic value of CONUT score combined with sICAM⁃1 in predicting peritoneal dialysis⁃associated peritonitis - LIU E，LIAO Chaoyan，LU Haixia，QIN Zuolian (Zhongguo linchuang yanjiu)
Objective To analyze the prognostic value of controlling nutritional status（CONUT）score combined with soluble intercellular adhesion molecule⁃1（sICAM⁃1）in predicting peritoneal dialysis⁃associated peritonitis（PDAP）.Methods A total of 176 patients with PDAP who received peritoneal dialysis treatment in the First Affiliated Hospital of Guangxi University of Chinese Medicine from January 2018 to December 2023 were selected. After admission，the clinical data，CONUT scores and sICAM⁃1 levels of the dialysis effluent of all patients were collected. The patients were followed up for 3 months to evaluate their prognosis and were divided into poor prognosis group（n=60）and good prognosis group（n=116）. The clinical data，CONUT scores and sICAM⁃1 levels of patients were compared between the two groups，and the related factors affecting the prognosis of PDAP patients were analyzed by multivariate logistic regression. Pearson correlation was used to analyze the relationship between CONUT scores and sICAM⁃ 1 levels.Receiver operateing characteristic（ROC） curve was used to analyze the prognostic value of CONUT score combined with sICAM⁃1 level in PDAP. Results Among the 176 PDAP patients，60 cases（34.09%）had poor prognosis. Multivariate logistic regression analysis showed that longer dialysis time，higher serum high⁃sensitivity C⁃reactive protein（hs⁃CRP）level，lower serum albumin level，higher CONUT score and higher sICAM⁃1 level were independent risk factors for poor prognosis in PDAP patients（P＜0.05）. Pearson correlation analysis showed that CONUT score was positively correlated with sICAM⁃1（r=0.657，P＜0.05）. The ROC curve results showed that the area under the curve（AUC）was higher when the CONUT score was 12 and the sICAM⁃1 was 8.62 ng/mL，with AUC values of 0.819 and 0.778，respectively. The combined AUC of these two was 0.847. Conclusion CONUT score combined with sICAM⁃1 can effectively predict the prognosis of patients with PDAP，and has high clinical application value. Long dialysis time，high serum hs⁃CRP level，low albumin level，high CONUT score，and high sICAM⁃1 level in dialysis effluent may lead to poor prognosis.